Evaluating the performance diagnostic checklist-human services to address performance issues of adults with intellectual disabilities. Issue 2 (3rd July 2022) - Hess, Brian H.; Walker, Seth G.; Sellers, Tyra P.
ABSTRACT: The Performance Diagnostic Checklist-Human Services (PDC-HS) is an informant-based tool used to assess performance issues in human service settings by identifying performance barriers and suggest matched interventions. There are few applications of the PDC-HS assessing performance in populations with intellectual disabilities. We used the PDC-HS to assess inaccurate book-shelf cleaning by three participants with intellectual disabilities in supported employment services at a library. We identified insufficient training and prompting as barriers to accurate and timely performance. We evaluated behavioral skills training, video modeling with voice-over instruction, and prompting on accuracy for all participants and timeliness for one participant. All participants exhibited increased accuracy on the shelf-cleaning task. One participant showed an increase in timeliness of completion, and one participant maintained and generalized performance after the training phase. Participants indicated positive experiences with the intervention. We discuss limitations and future directions of using the performance diagnostic checklists with individuals with intellectual disabilities.